2008
DOI: 10.1369/jhc.2008.951863
|View full text |Cite
|
Sign up to set email alerts
|

Factors in Tissue Handling and Processing That Impact RNA Obtained From Formalin-fixed, Paraffin-embedded Tissue

Abstract: S U M M A R Y Formalin-fixed, paraffin-embedded (FFPE) tissue is the most common specimen available for molecular assays on tissue after diagnostic histopathological examination. RNA from FFPE tissue suffers from strand breakage and cross-linking. Despite excellent extraction methods, RNA quality from FFPE material remains variable. To address the RNA quality factors within FFPE tissues, we studied RNA quality, isolating individual elements of the tissue fixation and processing including length of fixation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
141
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(152 citation statements)
references
References 16 publications
6
141
0
2
Order By: Relevance
“…11,24,25 Alternatively, immunostaining of On the basis of the principle of heat-induced antigenretrieval techniques, we previously demonstrated that the use of antigen-retrieval buffer (pH 10) containing 1% SDS combined with high temperature resulted in excellent protein-extraction yield from archival FFPE tissue sections, without changing the antigenicity. 19 Therefore, we used antigen-retrieval buffer (Tris-HCl, pH 10) and Tris-based buffer containing detergent (Tris/Tricine/SDS, pH 8.2) as test bleaching buffers in addition to PBS as a control to investigate their effect on melanin-bleaching efficiency and downstream applications. All three alkaline diluents for H 2 O 2 showed good quality of histomorphology ( Figure 2).…”
Section: The Melanin Bleaching Methods Enabled Dna Analysis In Archivamentioning
confidence: 99%
See 1 more Smart Citation
“…11,24,25 Alternatively, immunostaining of On the basis of the principle of heat-induced antigenretrieval techniques, we previously demonstrated that the use of antigen-retrieval buffer (pH 10) containing 1% SDS combined with high temperature resulted in excellent protein-extraction yield from archival FFPE tissue sections, without changing the antigenicity. 19 Therefore, we used antigen-retrieval buffer (Tris-HCl, pH 10) and Tris-based buffer containing detergent (Tris/Tricine/SDS, pH 8.2) as test bleaching buffers in addition to PBS as a control to investigate their effect on melanin-bleaching efficiency and downstream applications. All three alkaline diluents for H 2 O 2 showed good quality of histomorphology ( Figure 2).…”
Section: The Melanin Bleaching Methods Enabled Dna Analysis In Archivamentioning
confidence: 99%
“…[18][19][20] The specimens were rinsed briefly once in 100% ethanol, and then resuspended and ground in a solution of 4 M guanidine isothiocyanate, 20 mM sodium acetate, and 25 mM β-mercaptoethanol (pH 5.5) followed by 72 h incubation at 65°C with mild shaking. After incubation, RNA was isolated by phenol/chloroform extraction.…”
Section: Protein Extraction and Western Blottingmentioning
confidence: 99%
“…These are predominantly available as formalin-fixed paraffin-embedded (FFPE) tissues, which are suitable for IHC analysis, but due to the degradation and cross-linking present a technical challenge for nucleic acid analysis. 24 Several commercially available RNA assays based on detection of full-length E6/E7 transcripts, 25,26 as well as ''in house'' RNA assays based on detection of spliced E6*I/E7 transcripts, 15,16,27 have been described. These assays aim to amplify rather long cDNA sequence from cervical smear samples (up to 620 bp for full-length and up to 280 bp for spliced transcripts, respectively) and therefore are not suited for FFPE tissue analysis.…”
mentioning
confidence: 99%
“…Studies examining tissue fixation times and processing after collection suggest that fixation should commence as soon as possible but proceed no longer than 48 hours after collection. 46,47 With these data in mind, standardized protocols for efficient and effective tissue fixation and processing should be made available to pathologists and other public health professionals worldwide so as to provide high-quality tissue specimens that are ideal for use in both IHC and rRT-PCR assays.…”
Section: Discussionmentioning
confidence: 99%